Evaluation of Hypolipidemic Activity of Otolith Extracted from Catfish in Experimental Animals - Areqi, Abdullah Ahmed; Salih, A.M.M.; Mustafa, Nazik M.E; Ibrahim, Doaa Anwar (University of Science and Technology, Yemen, 2025)
Background: Otolith, also referred to as "ear stone", have been traditionally utilized in coastal regions, particularly in the Hodeida governorate, for managing diabetes mellitus. The local population believes that these structures possess numerous health benefit, including a purported ability to magically regulate diabetes and alleviate migraine headache pain. Objective: To investigate the hypolipidemic effects of Otolith as a novel traditional neutral agent obtained from catfish. Method: The 24 male rats were evenly divided into four groups six-rat in each. Control group (Group 1) received 0.9% w/v sodium chloride for 21 days. The remaining three groups received oral otolith at different doses for the same time. Group 2 (low dose) received 5g/day otolith per body weight. Mid-dose group 3 received 10 g/day otolith per body weight. Finally, Group 4, the high-dose group, received 15 g/day otolith per body weight. Lipid profile tests were done at the end of the experiment. Results: The findings indicate that Otolith markedly decreased triglycerides from 125.5 mg/dL (control) to 78.8 mg/dL (15 mg/day), cholesterol from 118.2 mg/dL to 69.67 mg/dL, and LDL from 54 mg/dL to 42.63 mg/dL, while elevating HDL from 28.5 mg/dL to 34 mg/dL at the maximum dosage (15 g/day). The dose-dependent enhancements were statistically significant P<0.05 for all, with the most notable effects observed at 15 g/day, suggesting Otolith's potential as a lipid-lowering agent. Conclusion: Otolith supplementation demonstrated a dose-dependent amelioration of lipid metabolism, marked by substantial decreases in total cholesterol, LDL, and triglyceride concentrations alongside elevated HDL levels. These beneficial effects were most pronounced at the maximum administered dosage (15 g/day), suggesting a potential therapeutic role in dyslipidemia management.